1991
DOI: 10.1161/01.str.22.6.785
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent influence of small changes in extracellular magnesium concentration on the tone of feline middle cerebral arteries.

Abstract: The aim of this study was to investigate the effect of small alterations in the extracellular magnesium concentration on the tone of feline middle cerebral arteries and to examine the role of the endothelium in these responses. We measured the isometric tension of isolated arterial rings placed between two stainless steel wires in a tissue chamber containing Krebs-Henseleit solution aerated with a gas mixture containing 95% O 2 and 5% CO 2 at 37°C. After precontraction with noradrenaline, a decrease of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…The facts seem to be incompatible with the reports that (27,28). Indeed, an acute decrease in extracellular Mg results in a transient relaxation followed by a sustained contraction in arteries with intact endothelium (29)(30)(31). It is possible that an increase in calcium influx caused by Mg removal may be transient and, therefore, the response by the release of EDRF cannot be detected in the present experimental condition where external Mg was removed 30 min before the addition of norepinephrine.…”
Section: Discussioncontrasting
confidence: 76%
“…The facts seem to be incompatible with the reports that (27,28). Indeed, an acute decrease in extracellular Mg results in a transient relaxation followed by a sustained contraction in arteries with intact endothelium (29)(30)(31). It is possible that an increase in calcium influx caused by Mg removal may be transient and, therefore, the response by the release of EDRF cannot be detected in the present experimental condition where external Mg was removed 30 min before the addition of norepinephrine.…”
Section: Discussioncontrasting
confidence: 76%
“…A direct relation between serum Mg levels and acute neurological events has not yet been described. However, Mg has been demonstrated to coregulate cerebrovascular smooth muscle tone, 14 and low serum Mg was associated with the development of cerebrovascular atherosclerosis. 6,7 There is some evidence supporting the hypothesis that dietary Mg intake potentially contributes to blood pressure and stroke reduction.…”
Section: Amighi Et Al Magnesium and Neurological Events 25mentioning
confidence: 99%
“…There is evidence to suggest that magnesium (Mg 2+ ) is bene®cial in the treatment of a number of conditions, including pre-eclampsia (Lucas et al, 1995;Eclampsia Trial Collaborative Group, 1995) and acute myocardial infarction (Woods et al, 1992). The mode of action of Mg 2+ in these conditions is not clear, although vasodilator properties of Mg 2+ are well documented both in vitro (Altura & Altura, 1980Altura & Turlapaty, 1981;Kimura et al, 1989;Skajaa et al, 1990;Szabo et al, 1991Szabo et al, , 1992Noguera & D'Ocon, 1993), and in vivo (Seelig et al, 1983;Dipette et al, 1987;Nishio et al, 1989;Chi et al, 1990;Ram et al, 1991;Sipes et al, 1991;Perales et al, 1991;Kemp et al, 1993Kemp et al, , 1994. Woods (1991) suggested that Mg 2+ is a coronary vasodilator, and that some of the bene®cial eect of Mg 2+ in the treatment of acute myocardial infarction may be due to the prevention and relief of coronary vasospasm associated with the condition.…”
Section: Introductionmentioning
confidence: 99%